Clusters of abusive parenting: a latent class analysis of families referred to Child Protective Services in Portugal - Matos, A. L.; Moleiro, C.; Dias, J. G. (Child Abuse and Neglect, 2014)
From the perspective of ecological models, it is suggested that a thorough behavior analysis of parental mistreatment and neglect is undertaken from a general approach to a more comprehensive and multi-dimensional perspective. Hence, the main goal of the present study was to determine if meaningful groups or clusters of abusive parenting in Portugal could be identified based on the characterization of the children and adolescents, their parents and context variables. An instrument was developed to assess variables of the children or adolescents, the family and the social context, all of which have been shown to be important in the literature. Child and Youth Protection Commissions from the whole of Portugal participated in the study, a total of 504 cases. Latent class analysis was applied in order to identify distinct parenting abusing behavior. The results showed four distinct clusters of families which are clearly defined in light of the types of risk and associated variables. The four groups are probabilistic and propose the composition of clusters with socio-demographic variables related to the types of risk. The significant interrelationships of different profiling characteristics are directly related to parenting abusing behavior. The results of this study confirmed our hypothesis of heterogeneous abusive parenting in Portugal. The findings yield useful policy-oriented results. Meaningfully organizing abusive parenting may be an important step not only in understanding the origins of abuse and neglect, but also in integrating this information into intervention models with children, young people and their families.